2002
DOI: 10.1104/pp.007526
|View full text |Cite
|
Sign up to set email alerts
|

F-Actin-Dependent Endocytosis of Cell Wall Pectins in Meristematic Root Cells. Insights from Brefeldin A-Induced Compartments

Abstract: (D.W.M.) Brefeldin A (BFA) inhibits exocytosis but allows endocytosis, making it a valuable agent to identify molecules that recycle at cell peripheries. In plants, formation of large intracellular compartments in response to BFA treatment is a unique feature of some, but not all, cells. Here, we have analyzed assembly and distribution of BFA compartments in development-and tissue-specific contexts of growing maize (Zea mays) root apices. Surprisingly, these unique compartments formed only in meristematic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
213
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(223 citation statements)
references
References 57 publications
3
213
1
3
Order By: Relevance
“…Double labelling of MPK6 and SCAMP1 clearly revealed their pronounced co-localization at TGN (Figure 9j-o, arrowheads). In order to localize Golgi we have used a commercial mouse monoclonal antibody 58 k. This antibody was previously shown to selectively label Golgi in lily pollen and maize root cells (Li and Yan, 2000;Baluška et al, 2002). As shown in Figure 9p-u, epidermal cells showed dispersed Golgi stacks within the cytoplasm.…”
Section: Mpk6 Localizes To Punctuated Structures Located At the Pm Anmentioning
confidence: 99%
“…Double labelling of MPK6 and SCAMP1 clearly revealed their pronounced co-localization at TGN (Figure 9j-o, arrowheads). In order to localize Golgi we have used a commercial mouse monoclonal antibody 58 k. This antibody was previously shown to selectively label Golgi in lily pollen and maize root cells (Li and Yan, 2000;Baluška et al, 2002). As shown in Figure 9p-u, epidermal cells showed dispersed Golgi stacks within the cytoplasm.…”
Section: Mpk6 Localizes To Punctuated Structures Located At the Pm Anmentioning
confidence: 99%
“…Endocytosis in plants has some parallels to the process in yeast, in particular its polymerized-actin dependence (42,43). The difficulties of overcoming high turgor pressure in plants by an actindependent process might thus be eased by a local turgor pressure reduction mechanism like that we discuss here for yeast.…”
Section: Application To Plant Cellsmentioning
confidence: 87%
“…Although no plasmamembrane-localized transporters that import GalA into the cytosol have been identified, a large gene family with over 50 monosaccharide transporter-like genes exist in Arabidopsis (34), perhaps one of them is GalA transporter. Baluska et al (35) have suggested that the pectic fragment can be endocytosed. Previous studies indicate that exogalacturonates are present in the cytosol of pollen (36).…”
Section: Enzyme Mutation Site Sugar Substratementioning
confidence: 99%